The chitinase bio-production ability of the Bacillus strain Q3 having the high antagonism toward fungi - Tran, Nguyen Thu; Dung, Nguyen Lan (Academia Journal of Biology, 2014)
In a trial study for the isolation of chitin-degrading bacteria from soil samples of agricultural fields from Hanoi city and Thaibinh, Hoabinh provinces, we have isolated 22 bacterial strains. Among these 22 strains, there was the Bacillus strain Q3 having the highest antagonism toward Fungi (Aspergilus VN04-460; Trichoderma VN04-412; Eurotium amstelodami; Eurotium chevalieri; Fusarium oxysporum) and the highest chitin hydrolyzis. On the MS medium with 0,2% colloidal chitin, the chitinase activity of the Bacillus strain Q3 culture reached the highest value after 48 hours, at 37°C and with pH 7.0.